Potret pengetahuan bidan Puskesmas/Desa dalam mendeteksi status gizi buruk pasca sosialisasi GEMPITA ASA di Provinsi Aceh - Azhari Azhari; Abdul Hadi; Arnisam Arnisam (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Midwives are the health professionals responsible for educating the public and recognizing nutritional issues in infants. The use of the MUAC scale is a straightforward and highly sensitive approach for detecting nutritional problems in toddlers. The use of the MUAC scale for toddlers is anticipated to provide an independent technique for detecting nutritional abnormalities in toddlers, particularly malnutrition.Objective: To describe the knowledge of midwives in Aceh Province on the detection of severely underweight and underweight using anthropometric indicators and the usage of the MUAC scale for toddlers.Method: This research is a cross-sectional examination of a program's effectiveness. This study's sample consisted of 553 community health center/village midwives from the Aceh province. The knowledge of midwives was assessed via a questionnaire administered following the